Evolution of circadian clock and light-input pathway genes in Hemiptera - Smykal, Vlastimil; Tobita, Hisashi; Dolezel, David (Insect biochemistry and molecular biology, 2025)
Circadian clocks are timekeeping mechanisms that help organisms anticipate periodic alterations of day and night. These clocks are widespread, and in the case of animals, they rely on genetically related components. At the molecular level, the animal circadian clock consists of several interconnected transcription-translation feedback loops. Although the clock setup is generally conserved, some important differences exist even among various insect groups. Therefore, we decided to identify in silico all major clock components and closely related genes in Hemiptera. Our analyses indicate several lineage-specific alterations of the clock setup in Hemiptera, derived from gene losses observed in the complete gene set identified in the outgroup, Thysanoptera, which thus presents the insect lineage with a complete clock setup. Nilaparvata and Fulgoroidea, in general, lost the (6-4)-photolyase, while all Hemiptera lost FBXL3, and several lineage-specific losses of dCRY and jetlag were identified. Importantly, we identified non-canonical splicing variants of period and m-cry genes, which might provide another regulatory mechanism for clock functioning. Lastly, we performed a detailed reconstruction of Hemiptera's light input pathway genetic repertoire and explored the horizontal gene transfer of cryptochrome-DASH from plant to Bemisia. Altogether, this inventory reveals important trends in clock gene evolution and provides a reference for clock research in Hemiptera, including several lineages of important pest species.
Keywords: Circadian Clocks; Gene loss; Hemiptera; Phylogeny; Insect Proteins; Cryptochrome; Evolution; hmyzí proteiny; Photolyase; Circadian clock; Animals; molekulární evoluce; Evolution, Molecular; zvířata; cirkadiánní hodiny; fylogeneze; Horizontal gene transfer